Variability in Benthic Ecosystem Functioning in Arctic Shelf and Deep-Sea Sediments: Assessments by Benthic Oxygen Uptake Rates and Environmental Drivers - Kiesel, Joshua; Bienhold, Christina; Wenzhöfer, Frank; Link, Heike (Frontiers in Marine Science, 2020)
Remineralization of organic matter at the seafloor is an important ecosystem function, as it drives carbon and nutrient cycling, supplying nutrients for photosynthetic production, but also controls carbon burial within the sediment. In the Arctic Ocean, changes in primary production due to rapid sea-ice decline and thinning affect the export of organic matter to the seafloor and thus, benthic ecosystem functioning.. Due to the remoteness and difficult accessibility of the Arctic Ocean, we still lack baseline knowledge about patterns of benthic remineralization rates and their drivers in both shelf and deep-sea sediments. Particularly comparative studies across regions are scarce. Here, we address this knowledge gap by contrasting benthic diffusive and total oxygen uptake rates (DOU and TOU), both established proxies of the benthic remineralization function, between shelf and deep-sea habitats of the Barents Sea and the central Arctic Ocean, sampled during a RV Polarstern expedition in 2015. DOU and TOU were measured using ex situ porewater oxygen microprofiles and sediment core incubations, respectively. In addition, contextual parameters including organic matter availability and microbial cell numbers were determined as environmental predictors. Pan-Arctic regional comparisons were obtained by extending our analyses to previously published data from the Laptev and Beaufort Seas. Our results show that 1) benthic oxygen uptake rates and most environmental predictors varied significantly between shelf and deep-sea habitats, 2) the availability of detrital organic matter is the main driver for patterns in total as well as diffusive respiration, while bacterial abundances were highly variable and only a weak predictor of differences in TOU and DOU, 3) regional differences in oxygen uptake across shelf and deep-sea sediments were mainly related to organic matter availability and may reflect varying primary production regimes and distances to the nearest shelf. Our findings suggest that the expected decline in sea-ice cover and the subsequent increase in export of organic matter to the seafloor may particularly enhance deep-sea remineralization in the deep Arctic Ocean, altering benthic ecosystem functioning in future climate scenarios.